Factors associated with Knowledge, Attitudes and Practice regarding organ donation in the general population in the West Bank, 2016 - Nidal AbuKahyzaran; Mohammad Hachem; Osama Hrub (My University, 2016)
Background Organ transplantation has become one of the most effective ways to decrease morbidity and mortality among patients with end-stage organ failure worldwide. However, many factors can affect the availability of organs and the donation attitude, limiting therefore the rates of survival for many patients. Assessing the knowledge, attitude and practice of Palestinian population towards Organ Donation (OD) may help to build a successful organ transplant program in the country. Methods A cross sectional descriptive, analytical study, using a validated questionnaire (Telephone based survey) was carried out among the general population of the West Bank in 2016. The questionnaire elicited information about sociodemographic data of participants and Knowledge, attitude and practice regarding organ donation. Descriptive, analytical and multivariate analyses were performed using The Stata Statistical Package v 20.Significance was considered at p value < 0.05. Results Of the 565 subjects contacted, 385 completed the survey (Response Rate = 68.14%). Mean age of participants was 42.15 years (SD=14.137). The majority of participants (97.4%) were Muslim and 69.09% were married. As for the educational level, 28.83% of the participants had an educational level below high school while 35.32% were university graduate and postgraduate. 80.8% were employed while 19.2% were not. 49.6% of the study participants were living in urban dwelling, 41.6% were living in rural areas and 8.8% were living in refugee camps. Local religious clergy was reported as being the source of general information by 40% of participants. 71% had an adequate knowledge towards OD. Of those, 64% believed OD carries some form of risk being general weakness the most frequent one. The most commonly selected organs/tissues were blood, kidneys and eyes and Television turned to be the most common source of information. Regarding the attitude towards OD, 81% had a positive attitude 61 (N=342) individuals would consider OD only to a close family member. As for the religion of the recipient, 48.91% would prefer to donate to a recipient of the same religion. In a living donation, 74.56% selected the donor as the one to give authorization for OD, but in donation from cadaver, 58.77% believed that the authorization to donate should be given by the donor’s close family. 77.78% believed that organ donation should be promoted. Regarding level of knowledge (adequate), bivariate analysis yielded that: gender, level of education, monthly income and marital status were found statistically significant (p value 0.008, 0.046, 0.041 and 0.012 respectively). Religious score, marital status and knowledge score were found to have a statistically significant association with a positive attitude to OD (p value 0.015, 0.031 and 0.003 respectively).The multivariate analysis for knowledge showed that only gender and level of education remains significantly associated with knowledge score while for attitude, marital status, knowledge score, religious score and living in refugee camp were found to be statistically significant. Conclusion The adequate knowledge and positive attitude and practice towards OD of the Palestinian population should be improved and encouraged by the authorities taking into account the mentioned factors affecting those dimensions in order to build and maintain a successful Organ Donation Program.